Butenolide derivatives from Aspergillus terreus selectively inhibit butyrylcholinesterase - Cui, Xiang; Deng, Shanshan; Li, Guoyin; Zhang, Yunxia; Wang, Lining; Wu, Changjing; Deng, Yanru (Frontiers in Chemistry, 2022)
Two undescribed butenolide derivatives, asperteretal J (1) and K (2), together with 13 known ones (3–15) were isolated from an endophytic fungus Aspergillus terreus SGP-1, the fermentation product of which exhibited selective inhibitory activity toward butyrylcholinesterase. The structures of the new compounds were elucidated based on HRMS and NMR data, and the absolute configurations were determined by specific optical rotation comparison. All compounds were evaluated for cholinesterase inhibitory effects with galantamine as a positive control. Compounds 4–8 selectively inhibited butyrylcholinesterase with IC50 values of 18.4–45.8 µM in a competitive manner, with Ki values of 12.3–38.2 µM. The structure-activity relationship was discussed. Molecular docking and dynamic simulation of the inhibitor-enzyme complex were performed to better understand the interactions.